Pemodelan dan Estimasi Sumberdaya Uranium di Sektor Lembah Hitam, Kalan, Kalimantan Barat - Muhammad, Adi Gunawan; Soetopo, Bambang (BRIN Publishing, 2016)
Lembah Hitam Sector is part of Schwaner Mountains and Kalan Basin upper part stratigraphy. Uranium (U) mineralization layer is associated with metasiltstone and metapelites schistose heading to N 265° E/60° S. Evaluation drilling carried out with a distance of 50 m from an existing point (FKL 14 and FKL 13) to determine the model and the amount of U resources in measured category. To achieve these objectives some activities including reviewing the previous studies, geological and U mineralization data collecting, grades quantitative estimation using log gross-count gamma ray, database and modeling creation and resource estimation of U carried out. Based on modeling on ten drilling data and completed with drilled core observation, the average grade of U mineralization in Lembah Hitam Sector obtained. The average grade is ranging from 0.0076 - 0.95 % eU3O8, with a thickness of mineralization ranging from 0.1 - 4.5 m. Uranium mineralization present as fracture filling (veins) or groups of veins and as matrix filling in tectonic breccia, associated with pyrite, pyrrhotite, magnetite, molybdenite, tourmaline and quartz in metasiltstone and metapelites schistose. Calculation of U resources to 26 ores body using 25 m searching radius resulted in 655.65 tons ores. By using 0.01 % cut-off grade resulted in 546.72 tons ores with an average grade 0.101 % eU3O8. Uranium resource categorized as low-grade measured resources.